EXPRESSIONS OF DISAGREEMENT IN THE INFO CEGATAN JOGJA FACEBOOK GROUP - Putra, Dona Aji Karunia; Suhandano, Suhandano; Sulistyowati, Sulistyowati (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
Disagreement is a difference of opinion expressed differently based on the media used. Based on this phenomenon, it is interesting to define an expression of disagreement and the types of discourse that trigger it on Facebook, which tends to be accessible and not distant. Analyzing these two things is interesting and important as something new in pragmatic studies. This study aims to define the expression of disagreement and describe the types of messages that get a lot of disagreement responses in the ICJ Facebook group. The current research utilized a qualitative approach with a descriptive method. The data in this study are messages and comments that contain disagreement in the ICJ Facebook group. Data collection was carried out using documentation, observation, and note-taking techniques. The data analysis technique utilizes semantic and pragmatic perspectives. The results showed that the expression of disagreement could be defined as a negative expression expressed verbally as a reaction when the speaker opposes or denies the opponent's proposition or vice versa in a communication context. Posts or messages that get a lot of disagreement responses have the following characteristics, 1) the topics discussed relate to the disclosure of social problems from a personal point of view, 2) aim to assess social phenomena or as social criticism, 3) type of expressive and persuasive discourse.